Oreocharis yunnanensis, a new name for the illegitimate Oreocharis glandulosa (Gesneriaceae) from China - Rossini, Josiene; Freitas, Joelcio (Phytotaxa, 2014)
Oreocharis Benth. (1876: 1021) comprises about 80 species of Gesneriaceae distributed in the Old World tropics and subtropics. Based on molecular and morphological analyses, Möller et al. (2011) proposed to include several genera and species of Chinese Gesneriaceae in Oreocharis to correspond to monophyly of the group. Among the newly proposed combinations the authors included Didissandra glandulosa Batalin (1892:175) = Oreocharis glandulosa (Batalin) Mich.Möller & A.Weber (in Möller et al. 2011: 21).